NIV-Helmet in Severe Hypoxemic Acute Respiratory Failure. (27th April 2015) - Martins, Joana; Nunes, P.; Silvestre, C.; Abadesso, C.; Loureiro, H.; Almeida, H.
Abstract : Noninvasive ventilation (NIV) is a method to be applied in acute respiratory failure, given the possibility of avoiding tracheal intubation and conventional ventilation. A previous healthy 5-month-old boy developed low-grade intermittent fever, flu-like symptoms, and dry cough for 3 days. On admission, he showed severe respiratory distress with SpO2 /FiO2 ratio of 94. Subsequent evaluation identified an RSV infection complicated with an increase of inflammatory parameters (reactive C protein 15 mg/dL). Within the first hour after NIV-helmet CPAP SpO2 /FiO2 ratio increased to 157. This sustained improvement allowed the continuing of this strategy. After 102 h, he was disconnected from the helmet CPAP device. The NIV use in severe hypoxemic acute respiratory failure should be carefully monitored as the absence of clinical improvement has a predictive value in the need to resume to intubation and mechanical ventilation. We emphasize that SpO2 /FiO2 ratio is a valuable monitoring instrument. Helmet interface use represents a more comfortable alternative for providing ventilatory support, particularly to small infants, which constitute a sensitive group within pediatric patients.